Descriptions of health by EU citizens begging abroad. Issue 1 (1st January 2017) - Wagman, Petra; Björklund, Anita; Johansson, Ann; Fristedt, Sofi
ABSTRACT: Poor citizens from European Union (EU) member countries begging to support themselves are now common in affluent EU countries. Their lack of basic amenities, such as access to a shelter and sanitation is not in line with human rights and also implies a risk for health issues. Despite this, we know little about how these vulnerable EU citizens, themselves, perceive their health situation. The aim of this study was to explore vulnerable EU citizens' descriptions of their health. Eight females and 12 males from Romania, 19–64 years of age, participated in individual interviews that included health issues. Qualitative content analysis was used, identifying the main category "Begging abroad and health - for better and for worse" together with two categories and five subcategories. It is concluded that EU citizens begging abroad risk poorer health as a consequence of their attempts to improve their situation, both their own health and that of their relatives. Therefore, they need access to affordable health care as this may decrease the need for unwanted travelling abroad to beg.